Direct preparation of fatty acid methyl esters and determination of in vitro antioxidant potential of lipid from fresh Sebal causarium Seed - Olubunmi ATOLANI, Oluwaseeni ADENIYI, Oluwatimilehin O. KAYODE, Charles B. ADEOSUN (Journal of Applied Pharmaceutical Science, 2015)
Classical method of sample preparation for fatty acid analysis is a complicated, rigorous, multiple-step process that is often time-consuming. However, innovation has made it possible to obtain fatty acids esters in a single step without compromise of the quality and quantity of the products obtained. Fatty acid methyl esters (FAMEs) were obtained from Sabal causiarum seed using direct trans-esterification method. The reaction was performed in a one necked glass reactor equipped with a reflux condenser. The composition of the FAMEs obtained was analyzed using GC-FID/GC-MS. The FAMEs was also evaluated for its antioxidant potential using DPPH assay while α- tocopherol served as a standard. From the Total ion chromatogram, a total of twelve fatty acids were identified with the dominant being linoleic acid (29.83%), an essential polyunsaturated omega-6 fatty acid. Other compounds obtained in significant yield include palmitic acid (20.75 %), dodecanoic acid (12.15 %), oleic acid, an omega-9 monounsaturated fatty acid (11.51%), 11-Octadecenoic acid (5.89 %), Ceric acid (4.97) and lignoceric acid (4.56 %). The oil had higher antioxidant potential (with IC50 value 0.19 ± 0.31 mg/mL) than the standard, alpha-tocopherol (with IC50 of 0.25 ± 0.4 (mg/mL). The direct trans-esterification method enables the quick determination of the fatty acid profile of Sabal causiarum seed. It is a viable method that saves time, limit use of solvents and reduce the possibility of contaminations that is associated with classical multistage procedure. The chemical composition and high antioxidant value of the oil is a strong indication of the future economical and biological relevance of the Sabal causiarum seed oil.
Keywords: Sabal causiarum, direct trans-esterification, FAMEs, antioxidant, essential fatty acid, Total ion chromatogram.